Learning path : Hadoop. - Morrow, Rick; Yaholom, David; Hanlon, Tom; Bengfort, Benjamin; Kim, Jenny; Grover, Mark; Shapira, Gwen; Seidman, Jonathan; Malaska, Ted; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"The standard for large-scale data processing, Hadoop makes your data truly accessible. This Learning Path offers an in-depth tour of the Hadoop ecosystem, providing detailed instruction on setting up and running a Hadoop cluster, batch processing data with Pig, Hive's SQL dialect, MapReduce, and everything else you need parse, access, and analyze your data."--Resource description page.
Learning Apache Hadoop / Rich Morrow -- Introduction to Hadoop YARN / David Yaholom -- Introduction to Apache Hive / Tom Hanlon -- Hadoop fundamentals for data scientists / Jenny Kim and Benjamin Bengfort -- Architectural considerations for Hadoop applications / Mark Grover, Gwen Shapira, Jonathan Seidman, and Ted Malaska.
Presenters, Rich Morrow, David Yaholom, Tom Hanlon, Jenny Kim, Benjamin Bengfort, Mark Grover, Gwen Shapira, Jonathan Seidman, and Ted Malaska.
Title and publication information from resource description page (Safari, viewed March 16, 2016).
Keywords: Apache Hadoop; Electronic data processing -- Distributed processing; Big data; MapReduce (Computer file); SQL (Computer program language); Electronic books